2021
DOI: 10.1128/jmbe.v22i1.2613
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Interrupted: How COVID-19 Turned Thoughts into Practice

Abstract: The Community College Anatomy and Physiology Education Research (CAPER) project is a 2-year grant that provides a variety of professional development opportunities to community college instructors of Anatomy and Physiology in the United States. Instructors who participate in the CAPER project also take part in a larger research study that uses both qualitative and quantitative methods to track the instructors’ progress with adapting new teaching methods into their classrooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Chemistry faculty at a private liberal arts college and their students developed a plan in 5 days to transition department classes online (19). Faculty from across the country who participated in the Community College Anatomy and Physiology Research (CAPER) project and professional development prior to and during the pandemic used their new skills that were more compassionate to the challenges students faced and integrated active learning strategies to their emergency remote teaching (20). In a PD course for chemistry graduate TAs at a private R1 university, the instructor highlighted wellness and community-building skills in addition to pedagogical and technical skills (21).…”
Section: Current Work Addressing the Problemmentioning
confidence: 99%
“…Chemistry faculty at a private liberal arts college and their students developed a plan in 5 days to transition department classes online (19). Faculty from across the country who participated in the Community College Anatomy and Physiology Research (CAPER) project and professional development prior to and during the pandemic used their new skills that were more compassionate to the challenges students faced and integrated active learning strategies to their emergency remote teaching (20). In a PD course for chemistry graduate TAs at a private R1 university, the instructor highlighted wellness and community-building skills in addition to pedagogical and technical skills (21).…”
Section: Current Work Addressing the Problemmentioning
confidence: 99%
“…A preliminary focus group by Whiteside et al (2020), for instance, suggested that the pandemic functioned as a vehicle of “disruptive innovation,” creating opportunities for empathy, collaboration, and support. This is further evinced by a growing number of studies documenting changes in teaching strategies, as well as blogs and reviews offering advice and best practices in engineering (Balakrishnan & Malim, 2020; Bennett et al, 2021; e.g., Clark & Besterfield‐Sacre, 2020; Culbert, 2021; Deutschman et al, 2021; Gelles et al, 2020; Jenkins, 2021; Marquez & Garcia, 2021; Park et al, 2020). Like much of the literature on crisis teaching produced before the pandemic, which focused on teaching in the context of acute traumas, such as school shootings, natural disasters, and terrorist attacks (e.g., Chodosh, 2002; Elbih, 2013; Foster, 2006), these publications largely emphasize course content and student outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of emergency remote teaching (ERT), as described by Hodges et al (2020), is distinct from conventional online teaching due to its urgency and the lack of infrastructure to support instructors. The transition online and the broader cultural climate during Spring 2020 generated an environment that forced instructors to reconsider aspects of their teaching (e.g., Cameron‐Standerford et al, 2020; Deutschman et al, 2021; Gelles et al, 2020; Kim et al, 2021; Leung et al, 2020). Universities responded by providing informal and formal skill‐swapping opportunities and offering feedback on class observations from expert staff (Clark & Besterfield‐Sacre, 2020; Whiteside et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La pandemia por COVID-19, que se iniciara en China a fines de 2019 y continua aún en 2021, ha impuesto un nuevo desafío para el mundo, en el que las Ciencias de la Salud se ven muy comprometidas tanto en la práctica professional, la investigación y la formación de recursos humanos. Los gobiernos impusieron restrictciones para evitar el contacto próximo entre las personas, y en este marco, la gran mayoría de las actividades comenzaron a desarrollarse a distancia, apelando al uso de la tecnología (Bond y Franchi, 2020;Dost et al, 2020;Longhurst et al, 2020;Pather et al, 2020;Puljak et al, 2020;Singal et al, 2020;Banovac et al, 2021;Deutschman et al, 2021;Pawlina, 2021;Shahrvini et al, 2021;Singal et al, 2021;Suarez-Escudero, et al, 2021) Las restricciones por la pandemia de COVID-19 en Argentina comenzaron el 20 de marzo del 2020, fecha similar a la mayoría de los países del mundo, solo que en las universidades argentinas aún no habían comenzado los cursos regulares del ciclo lectivo correspondiente a ese año. Prevalecían las medidas sanitarias y la educación fue relegada.…”
Section: Introductionunclassified